Vibrating vaginal balls to improve pelvic floor muscle performance in women after childbirth: a protocol for a randomised controlled feasibility trial. (28th December 2015) - Oblasser, Claudia; McCourt, Christine; Hanzal, Engelbert; Christie, Janice
Abstract: Aim: This paper presents a feasibility trial protocol the purpose of which is to prepare for a future randomised controlled trial to determine the effectiveness of vibrating vaginal pelvic floor training balls for postpartum pelvic floor muscle rehabilitation. Background: Vibrating vaginal pelvic floor training balls are available in Austria to enhance women's pelvic floor muscles and thus prevent or treat urinary incontinence and other pelvic floor problems following childbirth. Nonetheless, there is currently little empirical knowledge to substantiate their use or assess their relative effectiveness in comparison to current standard care, which involves pelvic floor muscle exercises. Design: Single blind, randomised controlled feasibility trial with two parallel groups. Methods: It is planned to recruit 56 postpartum women in Vienna, who will be randomised into one of two intervention groups to use either vibrating vaginal balls or a comparator pelvic floor muscle exercises for 12 weeks. As this is a feasibility study, study design features (recruitment, selection, randomisation, intervention concordance, data collection methods and tools) will be assessed and participants' views and experiences will be surveyed. Tested outcome measures, collected before and after the intervention, will be pelvic floor muscle performance as reported by participants and measured by perineometry. Descriptive and inferential statistics and content analysis will serve the preparation of the future trial. Discussion: The results of this feasibility trial will inform the design and conduct of a full randomised controlled trial and provide insight into the experiences of women regarding the interventions and study participation.